SLR : SPI Dan Kecurangan Akuntansi Terhadap Keamanan Data Dalam SIA Di Era BIG DATA - Fatrizia, Seftina; Arliana, Shafira Aulia (Politeknik Raflesia Press, 2023)
Technological advances in the big era have brought accounting to balance its existence as a discipline that continues to grow. Apart from the many conveniences experienced by users of the accounting information system (AIS), data security and the threat of cybercrime are new challenges for accountants to effectively strengthen the internal control system (SPI). Therefore this study aims to examine the role of SPI and accounting fraud on data security in AIS in the big data era. The method used is Systematic Literature Review with PRISMA. The results of the study showed that of the 200 articles downloaded, there were 34 articles that discussed indicators in this study, and only 25 articles met the inclusion and exclusion criteria. Based on the 25 articles, it explains that: (1) SPI can reduce accounting fraud that occurs in an organization; (2) technological advances increase data security threats in AIS; and (3) cyber crime cases can threaten data security in accounting information systems.